Some legal issues about bank guarantee to protect buyer's rights in buying and selling transactions of future conforming houses - Thanh , Le Minh (IHSA Institute, 2024)
In the context of strong development of the real estate market and technology, the application of guarantees in future housing transactions is becoming an important trend. Guarantees not only help increase transparency and safety for participating parties but also ensure fairness and protect the interests of buyers and sellers. With guarantee relationships in future housing sales transactions as a form of title insurance to protect property owners and home buyers from financial losses due to defects or issues related to property ownership. The article uses the method of analyzing written law, accessing secondary documents through Vietnamese practice on guarantees in future housing sales transactions and warning about some risks to protect rights. The buyer's benefits in the transaction of buying and selling houses to be formed in the future.